Monthly Bulletin of Statistics=Bulletin Mensuel de Statistique - United Nations (Newyork: United States, 2009)
The monthly Bulletin presents statistics for more than 200 countries and territories of the world.It contains monthly and/or annual and quartely data on a variety of subjects,including population,prices,employment and earnings,energy,manufacturing,transport,construction,international merchandise trade and finance.
Includes Bibliographical References
Keywords: Monthly Bulletin--Economic affairs; Monthly Bulletin--Social affairs